Peningkatan Kinerja Karyawan Melalui Motivasi dan Lingkungan Kerja Pada BMT Amanah Mandiri Purwantoro - Awwalin Sholihah; Muchtim Humaidi (Institut Agama Islam Negeri Ponorogo, 2023)
Effective utilization of human resources is a way for a company to maintain its survival and growth in the future. One way that can improve employee performance is by providing work motivation and conditioning the work environment. However, in reality, employees still lack discipline and their work productivity decreases. The problems studied in this study are how the motivation techniques and conditioning of the work environment are carried out, the obstacles faced, and the impact on improving employee performance at BMT Amanah Mandiri Purwantoro. In this study, the author used a type of field research with a qualitative approach. This study uses data collection methods carried out at the place where the phenomenon occurs, ranging from observation, interviews, and documentation. From the results of the research that the author conducted, it can be concluded that the motivation and conditioning techniques of the work environment provided are in accordance with the theory used starting from providing salaries, providing health guarantees, and also respecting and respecting each other. However, there are still some things that are still lacking, namely emotional changes in themselves, the condition of the building is less extensive, the provision of incentives received by employees is still not in accordance with their needs, and also the level of discipline that is still low both in the accuracy of entering work and completing work in accordance with the predetermined time.